Solid-State Synthesis and Characterization of a Copper(II) Complex with o-Vanillin - GUO, HANGMING; ZHAO, GUOLIANG (Asian Journal of Chemistry, 2010)
The complex, [Cu(C8H7O3)2H2O], has been synthesized by the solid-state reaction of copper acetate and o-vanillin (C8H8O3) ligand. The complex was characterized by X-ray powder diffraction, elemental analysis, FTIR spectra and TGDTG. The elemental analyses indicate 1:2 (metal:ligand) stoichiometry for the complex. The spectral studies show that the ligand acts as a bidentate ligand with the phenolic-CO and carbonyl group as coordinating donor sites and the H2O was coordinated with Cu(II) ion. The suggested coordination number is five in this complex.